Associations of executive function and age of first use of methamphetamine with methamphetamine relapse - Mu, Lin-Lin; Wang, Yan; Wang, Li-Jin; Xia, Ling-Ling; Zhao, Wei; Song, Pei-Pei; Li, Jun-Da; Wang, Wen-Juan; Zhu, Lin; Li, Hao-Nan; Wang, Yu-Jing; Tang, Hua-Jun; et al. (Frontiers in Psychiatry, 2022)
Background and aims: Methamphetamine (MA) is a psychostimulant associated with a high relapse rate among patients with MA use disorder (MUD). Long-term use of MA is associated with mental disorders, executive dysfunction, aggressive behaviors, and impulsivity among patients with MUD. However, identifying which factors may be more closely associated with relapse has not been investigated. Thus, we aimed to investigate the psychological factors and the history of MA use that may influence MA relapse. Methods: This cross-sectional study included 168 male MUD patients (MUD group) and 65 healthy male residents (control group). Each patient was evaluated with self-report measures of executive dysfunction, psychopathological symptoms, impulsiveness, aggressiveness, and history of MA use. Data were analyzed with t-tests, analyses of variance, and correlation and regression analyses. Results: The MUD group reported greater executive dysfunction, psychopathological symptoms, impulsivity, and aggression than the control group. Lower age of first MA use was associated both with having relapsed one or more times and with having relapsed two or more times; greater executive dysfunction was associated only with having relapsed two or more times. Conclusions: Patients with MUD reported worse executive function and mental health. Current results also suggest that lower age of first MA use may influence relapse rate in general, while executive dysfunction may influence repeated relapse in particular. The present results add to the literature concerning factors that may increase the risk of relapse in individuals with MUD.